PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN CURRENT RATIO (CR) TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR PERTAMBANGAN BATU BARA PERIODE 2016-2022 - Sekar Sari, Farhana Dita; Nasution, Raden (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to examine the effect of Return on Equity (ROE), Debt To Equity Ratio (DER) and Current Ratio (CR) on Stock Return in Coal Mining Subsector Companies Listed on the Indonesia Stock Exchange for the 2016-2022 Period. The research method used is a quantitative method with a verificative descriptive approach. The population in this study is coal mining subsector companies listed on the Indonesia Stock Exchange for the 2016-2022 period. The sampling technique used in this study was purposive sampling and was obtained by as many as 8 companies. Data analysis techniques are carried out by descriptive statistical analysis, classical assumption testing, verificative analysis and hypothesis testing with t test and F test using SPSS 26 software. The results of this study show that: (1) Return on Equity (ROE) partially has a significant positive effect on stock returns, (2) Debt to Equity Ratio (DER) partially does not have a significant effect on stock returns, (3) Current Ratio (CR) partially has a significant positive effect on stock returns, (4) Return on Equity (ROE), Debt to Equity Ratio (DER) and Current Ratio (CR) simultaneously have a significant effect on Stock Returns.